Experience of management of nasal foreign bodies in Out patient department of a Tertiary Hospital (Bangladesh Journal of Otorhinolaryngology, 2016)
Objectives: To evaluate 113 cases of nasal foreign body removal with regard to type of foreign body, location, complications, techniques for removal, age , genderand to present the results of theevaluation.Methods: Between April 2009 to May 2011, a total of 113 nasal foreign bodies were attended inOutpatient Department ofENT, Head and Neck Surgery in Sir Salimullah Medical College, MitfordHospital,Dhaka. A retrospective reviewwas undertaken to evaluate the parameters related to the nasal foreign body and their removal and the data wereanalyzed.Results:113 cases of nasal foreign bodies were attended in Outpatient department of ENT, Head and Neck Surgery in Sir Salimullah Medical College, Mitford Hospital, Dhaka. Of these 113 cases, 101cases were removed in outpatient department and 12 cases were admitted and were removed under general anaesthesia. We found higher incidence in patients between ages 2 and 5 years. The distribution of nasal foreign body was 44.25% in male and 55.75% in female.Conclusion:Nasal foreign bodies are encountered daily in our routine clinical practice in the pediatric age group. General anaesthesia is required in uncooperative agitated patients or impacted foreign body to avoid complications.Button batteries and penetrating foreign body must be treated immediately.Bangladesh J Otorhinolaryngol; October 2015; 21(2): 102-109